Heteroatom Doping: An Effective Way to Boost Sodium Ion Storage. Issue 27 (5th June 2020) - Li, Yu; Chen, Minghua; Liu, Bo; Zhang, Yan; Liang, Xinqi; Xia, Xinhui
Abstract: In response to the change of energy landscape, sodium‐ion batteries (SIBs) are becoming one of the most promising power sources for the post‐lithium‐ion battery (LIB) era due to the cheap and abundant nature of sodium, and similar electrochemical properties to LIBs. The electrochemical performance of electrode materials for SIBs is closely bound up with their crystal structures and intrinsic electronic/ionic states. Apart from nanoscale design and conductive composite strategies, heteroatom doping is another effective way to enhance the intrinsic transfer characteristics of sodium ions and electrons in crystal structures to accelerate reaction kinetics and thereby achieve high performance. In this review, the recent advancements in heteroatom doping for sodium ion storage of electrode materials are reviewed. Specifically, different doping strategies including nonmetal element doping (e.g., nitrogen, sulfur, phosphorous, boron, fluorine), metal element doping (magnesium, titanium, iron, aluminum, nickel, copper, etc.), and dual/triple doping (such as N–S, N–P, N–S–P) are reviewed and summarized in detail. Furthermore, various doping methods are introduced and their advantages and disadvantages are discussed. The doping effect on crystal structure and intrinsic electronic/ionic state are illustrated and the relationship with capacity and energy/power density is interrogated. Finally, future development trends in doping strategies for advanced SIBs electrodes are analyzed. Abstract : Heteroatom doping is an effective way to enhance the intrinsic transfer characteristics of sodium ions and electrons in crystal structures to accelerate reaction kinetics. Herein, an overview of recent advancements in understanding the heteroatom doping effect on sodium ion storage is presented. Different doping strategies are reviewed and summarized in detail. Future development trends in doping strategies are analyzed.